Vero cell assay for rapid detection of Clostridium perfringens enterotoxin. - Mahony, D E (1989)
A rapid assay which measured the biological activity of Clostridium perfringens enterotoxin was developed. The method involved the rapid killing of Vero cells by enterotoxin produced by C. perfringens grown in Duncan and Strong sporulation medium. Serial dilutions of toxin were added to Vero cells either in suspension or grown as monolayers in wells of a 96-well cell tissue culture cluster plate. Vital staining of Vero cells with neutral red, followed by extraction of the dye, allowed toxin levels to be determined either visually or by optical density measurements with a micro-ELISA M580 computer program. The toxin produced was confirmed as different from the Vero toxin of Escherichia coli and the alpha and theta toxins of C. perfringens.